A systematic review of economic evaluations of preoperative smoking cessation for preventing surgical complications. (August 2022) - McCaffrey, Nikki; Higgins, Julie; Greenhalgh, Elizabeth; White, Sarah L.; Graves, Nicholas; Myles, Paul S.; Cunningham, John E.; Dean, Emma; Doncovio, Sally; Briggs, Lisa; Lal, Anita
Abstract: Background: Whilst there is a substantial body of evidence on the costs and benefits of smoking cessation generally, the benefits of routinely providing smoking cessation for surgical populations are less well known. This review summarises the evidence on the cost-effectiveness of preoperative smoking cessation to prevent surgical complications. Materials and methods: A search of the Cochrane, Econlit, EMBASE, Health Technology Assessment, Medline Complete and Scopus databases was conducted from inception until June 23, 2021. Peer-reviewed, English-language articles describing economic evaluations of preoperative smoking cessation interventions to prevent surgical complications were included. Search results were independently screened for potentially eligible studies. Study characteristics, economic evaluation methods and cost-effectiveness results were extracted by one reviewer and details checked by a second. Two authors independently assessed reporting and methodological quality using the Consolidated Health Economic Evaluation Reporting Standards statement (CHEERS) and the Quality of Health Economic Studies Instrument checklist (QHES) respectively. Results: After removing duplicates, twenty full text articles were screened from 1423 database records, resulting in six included economic evaluations. Studies from the United States (n = 4), France (n = 1) and Spain (n = 1) were reported between 2009 and 2020. Four evaluations were conducted from a payer perspective. Two-thirds of evaluations were well-conducted (mean score 83) and well-reported (on average, 86% items reported). All studies concluded preoperative smoking cessation is cost-effective for preventing surgical complications; results ranged from cost saving to €53, 131 per quality adjusted life year gained. Conclusions: Preoperative smoking cessation is cost-effective for preventing surgical complications from a payer or provider perspective when compared to standard care. There is no evidence from outside the United States and Europe to inform healthcare providers, funders and policy-makers in other jurisdictions and more information is needed to clarify the optimal point of implementation to maximise cost-effectiveness of preoperative smoking cessation intervention. Systematic review registration number: PROSPERO 2021 CRD42021257740. Research registry registration number: reviewregistry1369. Highlights: Preoperative smoking cessation counselling & pharmacotherapy for 6–8 weeks is cost-effective vs standard care for preventing complications.[NM1] [NM1]. Evidence is derived from a relatively small number of studies largely conducted in the Unites States (US). Information about different combinations of high intensity smoking cessation interventions in other countries would be valuable.